Writing from the Margins of Media: Screenwriting Practice and Discourse During the First Indian Talkies. (December 2018) - Sengupta, Rakesh
This article is an attempt to rethink the intermedial practice and discourse of screenwriting during the first Indian talkies through a study of the margins of print, theatre and film history. I engage with the unfortunate archival absence of film scripts from the early years as a heuristic rather than a handicap, employing intermediality both as an archaeological and a conceptual tool in reconstituting screenwriting as a converged media practice. I argue that the widespread circulation of screenwriting manuals for amateurs constituted a pedagogical infrastructure separate from, but parallel to, the other infrastructural flow of ideas and professionals from the Parsi theatre into the film industry. The autobiographical accounts of some of the first playwright-turned-screenwriters bear testimony to the spaces they negotiated for themselves in the talkies after a successful stint with the Parsi stage. These memoirs form an interesting counterpoint to the testimonies of another group of screenwriters from the Indian Cinematograph Committee evidences (1927–1928) in which these writers express great apathy towards the practice in the Indian studios and declare their freelancing associations with Hollywood studios which solicited story ideas from viewers worldwide.